An investigation into the supposed loss of the Khoikhoi traditional religious heritage amongst its descendants, namely the Coloured people with specific references to the question of religiosity of the Khoikhoi and their disintegration - Nissen, Andrew Christoffel (Department of Religious Studies, 2016)
Bibliography: pages 94-97.